Relationship between peer group size and active outdoor play in children aged 9-12 years - Kazuya Tamura; Yuya Ueda; Takashi Saito; Ryo Goto; Naoki Yamada; Kiyomasa Nakatsuka; Kazuaki Uchida; Kana Horibe; Kenta Saeki; Haruhi Encho; Masato Tezuka; Mao Mukaijo; et al. (Japanese Society of Physical Fitness and Sports Medicine, 2023)
Outdoor play during childhood is vital for physical, cognitive, and social development. Outdoor play is influenced by friends, though the relationship between outdoor play and the number of close friends is not clear. This study aimed to investigate the association between peer group size and outdoor play among children aged 9-12 years. This study was cross-sectional in design. We recruited fourth- to sixth-grade children from two public elementary schools. Outdoor play contents and duration on weekdays were collected via a questionnaire, and the total duration of outdoor play on five weekdays was calculated. We asked the children to nominate up to 10 of their closest friends. We calculated the peer group size as the total number of reciprocal closest friends for each child. A multivariate linear regression analysis was conducted to investigate the association between peer group size and outdoor play duration, adjusted for gender, grade, school, body mass index, sports club participation, and screen time. This study included 291 children (137 girls, mean age: 10.6 ± 1.0 years). The peer group size was associated with outdoor play duration after adjusting for confounding factors (β: 0.18, 95% CI: 0.07-0.30). This study revealed that children aged 9-12 years, with larger peer group size showed a significantly longer duration of outdoor play.